2014
DOI: 10.1007/s00726-014-1847-3
|View full text |Cite
|
Sign up to set email alerts
|

Is d-aspartate produced by glutamic-oxaloacetic transaminase-1 like 1 (Got1l1): a putative aspartate racemase?

Abstract: d-Aspartate is an endogenous free amino acid in the brain, endocrine tissues, and exocrine tissues in mammals, and it plays several physiological roles. In the testis, d-aspartate is detected in elongate spermatids, Leydig cells, and Sertoli cells, and implicated in the synthesis and release of testosterone. In the hippocampus, d-aspartate strongly enhances N-methyl-d-aspartate receptor-dependent long-term potentiation and is involved in learning and memory. The existence of aspartate racemase, a candidate enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Moreover, we observed that acute D-Asp administration also elicits a transient increase of extracellular L-Asp, without affecting the amount of this L-amino acid in homogenates. To explain this data, we suggest that abnormal accumulation of D-Asp in the brain may perturb one or more of the still unclear cellular mechanisms regulating the local racemization of D-Asp into L-Asp2829, L-Asp vesicular storage3031 and release32. In addition, we cannot exclude that non-physiological, high D-Asp extracellular concentration may displace L-Asp from its binding to L-Glu/L-Asp transporters, which regulate the uptake of both Asp enantiomers33, thus resulting in increased extracellular L-Asp levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we observed that acute D-Asp administration also elicits a transient increase of extracellular L-Asp, without affecting the amount of this L-amino acid in homogenates. To explain this data, we suggest that abnormal accumulation of D-Asp in the brain may perturb one or more of the still unclear cellular mechanisms regulating the local racemization of D-Asp into L-Asp2829, L-Asp vesicular storage3031 and release32. In addition, we cannot exclude that non-physiological, high D-Asp extracellular concentration may displace L-Asp from its binding to L-Glu/L-Asp transporters, which regulate the uptake of both Asp enantiomers33, thus resulting in increased extracellular L-Asp levels.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, glutamic-oxaloacetic transaminase-1 like 1 (Got1l1) was identified as a putative aspartate racemase and is involved in adult neurogenesis. 79 A later study, however, demonstrated that systemic knockout of Got1l1 in mice does not alter the level of d-Asp in the brain or testis, 80 indicating the presence of an unknown authentic synthetic enzyme in mammals. Interestingly, recent studies suggest that mammalian serine racemase (SR), an endogenous synthetic enzyme for d-Ser, 81 is involved, at least in part, in d-Asp synthesis in the brain but not in the testis.…”
Section: Physiological Role Of D-aspartate In Mammals: Neurogenesis Amentioning
confidence: 97%
“…Moreover, contrary to the long-standing belief that NMDA is not endogenous in mammals, d -aspartate was also suggested to be a precursor to NMDA in rats [ 44 ]. Although serine racemase, to a degree, is able to produce d -aspartate from l -aspartate, the main synthetic pathway for d -aspartate remains an open question since reports of an aspartate racemase have been questioned [ 36 , 45 , 52 , 53 , 54 ]. However, to the best of our knowledge, like l -aspartate, the transporter responsible for loading d -aspartate into vesicles has not been identified.…”
Section: Amino Acidsmentioning
confidence: 99%